Grounding perceptions: the value of otoendoscopy images in strengthening parents and children's understanding and decision making in a pediatric ENT clinic - Carter, Bernie; Hampton, Thomas; Sharma, Sunil; De, Sujata (Frontiers in Communication, 2023)
In recent years, there has been increasing use of otoendoscopy in middle ear surgery. There is also increasing evidence of its usefulness as a diagnostic tool for clinicians. However, there is limited evidence on whether understanding their ear condition is of benefit to patients. This novel study sought to explore the perceptions, perspectives and satisfaction of parents, children and young people regarding the use of otoendoscope images in outpatient ENT consultations in relation to their understanding of ear symptoms, disease and subsequent treatment. The framework for the study is child (and parent) health literacy and that visual images can play in scaffolding understanding, communication, and decision-making. This qualitative descriptive, exploratory study used semi-structured observation, survey, short conversational interviews, and child activities. Purposive sampling of 16 children (aged 4-15yrs, various diagnoses) and parents/carers attending outpatient ENT clinic at a tertiary paediatric hospital. One overarching theme – ‘Grounding perceptions and deepening engagement’ - and two sub-themes ‘Strengthening understanding’ and ‘Supporting decision-making’ were identified. The children and parents valued the opportunity to see the images and gain insight and knowledge of their child’s pathology. The images appeared to promote child (and parent) health literacy and interaction between the child-parent-clinician and informed shared decision-making. This study suggests that the use of otoendoscopy in an out-patient setting and sharing of the images with parents, children and young people has a largely positive impact on understanding, relationship building and decision making in paediatric ENT consultations.